2015
DOI: 10.1038/nature14052
|View full text |Cite
|
Sign up to set email alerts
|

Commensal–dendritic-cell interaction specifies a unique protective skin immune signature

Abstract: The skin represents the primary interface between the host and the environment. This organ is also home to trillions of microorganisms that play an important role in tissue homeostasis and local immunity1–4. Skin microbial communities are highly diverse and can be remodelled over time or in response to environmental challenges5–7. How, in the context of this complexity, individual commensal microorganisms may differentially modulate skin immunity and the consequences of these responses for tissue physiology re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
637
1
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 665 publications
(666 citation statements)
references
References 37 publications
19
637
1
9
Order By: Relevance
“…Thus, it is yet unclear whether it is the microbial constituents of the intestine or of the skin that can promote alloreactivity. Indeed, defined skin commensals have recently been shown to modify local cutaneous immunity, affecting skin DCs and resident T cells and enhancing barrier immunity (13). The intestinal microbiota have also been shown to affect immunity as distal as the peripheral joints or the central nervous system in models of autoimmune arthritis or autoimmune encephalomyelitis (14,15).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is yet unclear whether it is the microbial constituents of the intestine or of the skin that can promote alloreactivity. Indeed, defined skin commensals have recently been shown to modify local cutaneous immunity, affecting skin DCs and resident T cells and enhancing barrier immunity (13). The intestinal microbiota have also been shown to affect immunity as distal as the peripheral joints or the central nervous system in models of autoimmune arthritis or autoimmune encephalomyelitis (14,15).…”
Section: Resultsmentioning
confidence: 99%
“…The combination of local immune surveillance in low-inflammatory settings brings into play other scenarios, such as infection with commensal microorganisms. Naik et al (87) showed that skin infection with selected strains of the commensal bacteria Staphylococcus epididymis resulted in accumulation of IL-17-producing, intraepithelial CD8 + CD103 + T cells in the absence of overt inflammation. Although the experiments did not formally identify these as CD8 + T RM cells, their intraepithelial localization and CD103 expression heavily implied that they were indeed nonmigratory memory cells sequestered from the circulation.…”
Section: T Rm Cells Are Specialized For the Control Of Sequestered Pmentioning
confidence: 99%
“…Employing laser capture microdissection of these compartments followed by 16S rRNA sequencing, Nakatsuji et al (2013) provided a potential mechanism by which microbes or their products may physically interact with immune cells in tissues previously believed to be sterile in order to exert an effect on the host. Indeed, colonization with a human commensal skin microbe, namely, Staphylococcus epidermidis, tunes T-cell homing and function in an IL-1-dependent manner in mice (Naik et al 2012(Naik et al , 2015. On the other hand, deficiencies in immunity have been shown in humans and mice to result in altered cutaneous microbial communities (Chehoud et al 2013;Oh et al 2013).…”
Section: The Ecology Of the Human Skinmentioning
confidence: 99%